Analysis of Dermatologic Events in Vemurafenib‐Treated Patients With Melanoma. (1st March 2013) - Lacouture, Mario E.; Duvic, Madeleine; Hauschild, Axel; Prieto, Victor G.; Robert, Caroline; Schadendorf, Dirk; Kim, Caroline C.; McCormack, Christopher J.; Myskowski, Patricia L.; Spleiss, Olivia; Trunzer, Kerstin; Su, Fei; et al.
Abstract : Background: Vemurafenib has been approved for the treatment of patients with advanced BRAF V600E ‐mutant melanoma. This report by the Vemurafenib Dermatology Working Group presents the characteristics of dermatologic adverse events (AEs) that occur in vemurafenib‐treated patients, including cutaneous squamous cell carcinoma (cuSCC). Methods: Dermatologic AEs were assessed from three ongoing trials of BRAF V600E mutation‐positive advanced melanoma. Histologic central review and genetic characterization were completed for a subset of cuSCC lesions. Results: A total of 520 patients received vemurafenib. The most commonly reported AEs were dermatologic AEs, occurring in 92%–95% of patients. Rash was the most common AE (64%–75% of patients), and the most common types were rash not otherwise specified, erythema, maculopapular rash, and folliculitis. Rash development did not appear to correlate with tumor response. Photosensitivity occurred in 35%–63% of patients, and palmar‐plantar erythrodysesthesia (PPE) occurred in 8%–10% of patients. The severity of rash, photosensitivity, and PPE were mainly grade 1 or 2. In all, 19%–26% of patients developed cuSCC, mostly keratoacanthomas (KAs). The majority of patients with cuSCC continued therapy without dose reduction after resection. Genetic analysis of 29 cuSCC/KA samples demonstrated HRAS mutations in 41%. Conclusions: Dermatologic AEs associated with vemurafenib treatment in patients with melanoma were generally manageable with supportive care measures. Dose interruptions and/or reductions were required in <10% of patients. Abstract : Vemurafenib has been approved for the treatment of patients with advanced BRAF V600E ‐mutant melanoma. The most commonly reported adverse events were dermatologic conditions, occurring in 92%–95% of patients. Dose interruptions and/or reductions were required in <10% of patients. Abstract : 摘要 背景 . 维罗非尼已获批用于晚期BRAF V600E 突变黑色素瘤患者的治疗。本项维罗非尼皮肤工作组报告描述了接受维罗非尼治疗患者的皮肤不良事件（AE）特征，包括出现皮肤鳞状细胞癌（cuSCC）。 方法 . 本研究对3项正在进行的BRAF V600E 突变阳性晚期黑色素瘤试验中的皮肤AE进行了评估。对cuSCC病灶亚组进行了组织学中心评估和遗传学特征分析。 结果 . 共 520 例患者接受维罗非尼治疗。最常见AE为皮肤AE，发生率为92% 95%。其中常见者为皮疹（64% 75%），最常见类型包括未作特别说明的皮疹、红斑、斑丘疹与毛囊炎。皮疹发生与肿瘤缓解无关。35% 63%的患者出现光敏性反应，8% 10%的患者出现掌跖红肿（PPE）。皮疹、光敏性反应及PPE多为1 2级。总体而言，19% 26%的患者出现cuSCC，大部分为角化棘皮瘤（KA）。绝大多数cuSCC在手术切除后仍以原剂量维罗非尼继续治疗。29例cuSCC/KA样本基因检测显示，41%出现 HRAS 突变。 结论 . 黑色素瘤患者中，维罗非尼相关皮肤AE通常可采用支持治疗措施处治，但<10%的患者需要停药和/或减量治疗。